IoT for wheel alignment monitoring system - Mohamad Hadi Sulaiman; Suhana Sulaiman; Azilah Saparon (International Journal of Electrical and Computer Engineering (IJECE), 2021)
A great deal of previous research into wheel alignment has focused on techniques of the alignment, which involve big, bulky and high cost to maintain. Even though several approaches are required, the works are tedious and only performed in spacious area and trained mechanics. IoT is the alternatives due to the evolution of smartphone with numerous sensors to support and assist the research and development for IoT applications in vehicles. In this work, smaller and portable wheel alignment monitoring system is introduced by using communication protocol between sensors, microcontroller and mobile phone application. Thus, graphical user interface (GUI) is utilized to the system via wireless communication technology using TCP/IP Communication Protocol. The system has been tested to suit the functioning architecture system for the wheel alignment to provide the user awareness on early detection of wheel misalignment. In addition, the application has been successfully integrated with Android mobile application via TCP/IP communication protocol and view the results in smart phone in real-time.